Confidence measures for large vocabulary continuous speech recognition. - Wessel, F.
In this paper, we present several confidence measures for large vocabulary continuous speech recognition. We propose to estimate the confidence of a hypothesized word directly as its posterior probability, given all acoustic observations of the utterance. These probabilities are computed on word graphs using a forward-backward algorithm. We also study the estimation of posterior probabilities on N-best lists instead of word graphs and compare both algorithms in detail. In addition, we compare the posterior probabilities with two alternative confidence measures, i.e., the acoustic stability and the hypothesis density. We present experimental results on five different corpora: the Dutch ARISE 1k evaluation corpus, the German Verbmobil '98 7k evaluation corpus, the English North American Business '94 20k and 64k development corpora, and the English Broadcast News '96 65k evaluation corpus. We show that the posterior probabilities computed on word graphs outperform all other confidence measures. The relative reduction in confidence error rate ranges between 19% and 35% compared to the baseline confidence error rate
Keywords: Dutch ARISE 1k evaluation corpus; English Broadcast News '96 65k evaluation corpus; English North American Business '94 20k corpus; English North American Business '94 64k corpus; German Verbmobil '98 7k evaluation corpus; N-best lists; Acoustic stability; Confidence measures; Error rate; Forward-backward algorithm; Hypothesis density; Hypothesized word; Large vocabulary continuous speech recognition; Posterior probability; Utterance; Word graphs